The Komunikasi Efektif dan Kerja Sama PKK Kelurahan Kampung Kajanan, Buleleng, Bali dalam Konsumsi Pangan B2SA - Siti Amanah; Yayuk Farida Baliwati; Titania Aulia; Rafnel Azhari (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Effective communication and collaboration are crucial for the successful implementation of the 10 Family Welfare Empowerment Programs (PKK). Among these, one key program focused on food. This community service program (PkM) aims to enhance PKK communication in collaboration with diverse, nutritious, balanced, healthy, and safe food consumption (B2SA). Unfortunately, the recommended standards for food consumption have not been adopted sufficiently. PkM employed action research approaches in Kampung Kajanan Village, Buleleng District, Bali. The project progresses through the Plan, Do, Study, and Action (PDSA) stages. These activities included training sessions, participatory observations, mentoring, and reflection. Data and information were collected from 30 PKK members, informants consisting of community leaders, and integrated service post (Posyandu) personnel. Pre- and post-test forms were employed to assess changes in knowledge, attitudes, and skills related to communication and collaboration. The data were analyzed through effective communication and collaboration analysis to facilitate behavioral transformation in the preparation of the B2SA menus. The findings from this community service reveal that PKK's internal and external communication is effective within routine activities, such as monthly meetings and informational exchanges about government programs; however, it is less effective in educating the community about B2SA food consumption. Internal collaboration was rated moderate. PKK engages in external communication with the local women’s group, focusing on processed foods. In conclusion, communication regarding B2SA foods is inadequate and requires enhancement through various channels and media. Support from the local government and the business sector is essential for improvement.